Analyzing the Correlation Between Self-Esteem, Self-Confidence, and Academic Achievement in Biology - Restuhati, Githa; Suprapto, Purwati Kuswarini; Ali, Mufti (Universitas Lampung, 2023)
This research is a correlational study that aims to determine the correlation between self esteem and self confidence with biology learning outcomes. The research sample was 58 students by purposive sampling. Data collection techniques used questionnaires and documentation of final biology semester assessment scores in odd semesters. The research instrument was a self esteem questionnaire with 23 statement items and a self confidence questionnaire with 21 statement items. The data analysis techniques used are the Pearson’s correlation test and regression test. Based on the research results, it shows that there is a relationship between self esteem and self confidence and student learning outcomes. The correlation coefficient (R) is 0.369, which means the relationship between the three variables is low. In addition, the coefficient of determination (R²) is 0.137, which means that the contribution of self esteem and self confidence to learning outcomes was 13.7%.Keywords: self-esteem, self-confidence, learning outcomes